Methodical guidelines for seminar classes and independent work on "History of University education" - Shyshkina, Y. K. (National Technical University "Kharkiv Polytechnic Institute", 2024)
The search for new opportunities for further civilizational development is one of the most pressing problems. In the past, the institution of higher learning has played an important part in shaping social, political, and cultural trends. The discipline “History of University Education” covers the development of education from ancient times to the present. During its study, students will get acquainted with the most well-known Universities of the world and will be able to critically assess the role of high education in development of the world. The means to achieve this will be an essay on a proposed or self-selected topic in the form of an abstract.
Keywords: methodical guidelines; fist higher educational establishments; the oldest universities in the world; university education of renaissance; modern universities; Bologna process; university education in Ukraine